Pengaruh Corporate Governance Terhadap Tax Avoidance Pada Perusahaan Asuransi di Indonesia - Helsa Titania Lestari; Debbi Chyntia Ovami (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to determine the effect of corporate governance (institutional ownership, the proportion of independent commissioners and board of directors) on tax avoidance in insurance companies listed on the Indonesia Stock Exchange in 2017-2019. The research method used by researchers is quantitative methods. The research population is all insurance sub-sectors listed on the Indonesia Stock Exchange in 2017-2019 as many as 16 companies. The research sample consists of 14 companies with annual reports for 3 years, namely from 2017-2019 with a total of 42 samples in the form of an annual report. The results show that partially institutional ownership has a positive and insignificant effect on insurance companies listed on the Indonesia Stock Exchange in 2017-2019, the proportion of independent commissioners partially has a significant negative effect on insurance companies listed on the Indonesia Stock Exchange 2017-2019 while the board of directors has a negative effect. insignificant for insurance companies listed on the Indonesia Stock Exchange in 2017-2019. Simultaneously, corporate governance (institutional ownership, proportion of independent commissioners and board of directors) has a significant effect on tax avoidance in insurance companies listed on the Indonesia Stock Exchange in 2017-2019.